Apakah Kompetensi, Motivasi, dan Kultur Organisasi Berdampak pada Profesionalisme Pegawai Bappeda Kabupaten Bener Meriah - Basri, Hasimi; Simahatie, Mai; Hildani, Hildani (Aceh Cooperative Care, 2025)
This study aims to demonstrate the impact of competency, motivation, and organizational culture on employee professionalism. A survey was conducted at the Bener Meriah Regency Bappeda office with 47 employees. A quantitative associative method was used, with path analysis used for data analysis. The results indicate: (1) a causal relationship exists between the variables Competence and Motivation, and organizational culture is moderate. (2) Employee competency has a direct and indirect impact on professionalism, with a contribution of 43.65%. (3) Motivation contributes 29.14%, and organizational culture contributes 26.76%. (4) Employee competency, motivation, and organizational culture simultaneously contribute positively to the professionalism of Bappeda Bener Meriah employees, with a contribution of 37.6%.